2018
DOI: 10.1111/nyas.13528
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the determinants of hemoglobin and iron status: adolescent–adult women comparisons in SANHANES‐1

Abstract: The study compared hemoglobin (Hb) and serum ferritin levels between adolescent and adult women with different body mass indices, dietary intake, and sociodemography. A secondary analysis of data for 3177 South African women ⩾15 years of age who participated in the SANHANES-1 study was undertaken. Abnormal Hb (≤12 g/dL) and serum ferritin (<15 μg/mL) were based on the World Health Organization's criteria for nonpregnant women aged ⩾15 years. Data were analyzed using STATA version 11. Overall, anemia was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 30 publications
7
19
0
2
Order By: Relevance
“…In addition to biomedical in uences, we also found that adolescents from higher-income households or whose mothers had higher educations were less likely to be anemic, which is in accord with other studies [6,11]. Similar results were observed when using the continuous Hb as the outcome.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition to biomedical in uences, we also found that adolescents from higher-income households or whose mothers had higher educations were less likely to be anemic, which is in accord with other studies [6,11]. Similar results were observed when using the continuous Hb as the outcome.…”
Section: Discussionsupporting
confidence: 92%
“…developmental stages of puberty are signi cantly associated with anemia, studies reported differential associations between puberty development and adolescent anemia among boys and girls [9]. Some studies reported that factors associated with anemia among adolescents were different from those in other populations and ages [10,11], highlighting the essence of examining population-speci c factors. Given that iron de ciency is a key factor contributing to anemia [12] and that adolescence is a critical period of diet transition from childhood to adulthood [13,14], improving adolescent dietary intake is likely a reasonable approach for preventing anemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in the study results, prevalence of anaemia among women aged over 10 y was 9.8%. These findings support that anaemia occurs more frequently in adolescents and women of reproductive age [9,10]. After adjusting for age, results showed that women with prevalence of anaemia had 31% lower odds of sitting for ≥ 7 h/d than those without anaemia.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, excessive sitting time can increase cardiovascular disease risk [7,8]. Therefore, anaemia may lead to prolonged sedentary time among women due to several factors such as development of menstrual disorders and pregnancy [9,10].…”
Section: Introductionmentioning
confidence: 99%